Prospective evaluation of oral premalignant lesions using a multimodal imaging system: a pilot study. Issue 2 (17th October 2019) - Yang, Eric C.; Vohra, Imran S.; Badaoui, Hawraa; Schwarz, Richard A.; Cherry, Katelin D.; Jacob, Justin; Rodriguez, Jessica; Williams, Michelle D.; Vigneswaran, Nadarajah; Gillenwater, Ann M.; Richards‐Kortum, Rebecca R.
Abstract: Background: Multimodal optical imaging, incorporating reflectance and fluorescence modalities, is a promising tool to detect oral premalignant lesions in real‐time. Methods: Images were acquired from 171 sites in 66 patient visits for clinical evaluation of oral lesions. An automated algorithm was used to classify lesions as high‐ or low‐risk for neoplasia. Biopsies were acquired at clinically indicated sites and those classified as high‐risk by imaging, at the surgeon's discretion. Results: Twenty sites were biopsied based on clinical examination or imaging. Of these, 12 were indicated clinically and by imaging; 58% were moderate dysplasia or worse. Four biopsies were indicated by imaging evaluation only; 75% were moderate dysplasia or worse. Finally, four biopsies were indicated by clinical evaluation only; 75% were moderate dysplasia or worse. Conclusion: Multimodal imaging identified more cases of high‐grade dysplasia than clinical evaluation, and can improve detection of high grade precancer in patients with oral lesions.